Qualitative and quantitative analyses of particulate flows in rotating drums using a DEM-based approach - (:unkn) unknown (Springer Nature Switzerland, 2024)
In mineral processing, ore grinding is an energy-intensive process. Tumbling mills used in grinding processes can be accounted for as rotating drums with liners. As part of an effort to evaluate ways of reducing energy consumption in such systems, theref...
Keywords: Flujos particulados; Método DEM